Viral reservoirs, latency and mechanisms of HIV persistence - Siliciano, Robert (Henry Stewart Talks, 2007)
Viral dynamics in patients on antiretroviral drugs, CD4+ T-cells, Response of resting T-cells to AG, Establishment and maintenance of a latent reservoir, Dynamics of the latent pool, HIV evolution, HAART, Residual viremia and blips on patients on HAART, The nature of blips, Blips do not represent clinically significant elevations in viremia, Characteristics of the PPC, The latent reservoir is not replenished by ongoing viral replication in patients on HAART
Archived at 2018/12/10